Drawbacks of the academic style in students’ works - Macienė, Jurgita (Information & Media, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]The academic writing style tends to have quite clearly described requirements. University students use academic writing when doing course papers and theses. The goal of this article is to analyze the drawbacks of the academic style in examples of students’ works, identify the ways in which they are inappropriate and to suggest options for correcting the drawbacks. When reading the course papers and final theses, one can notice that students do not follow the foundational requirements of academic writing – such as clarity, accuracy, conciseness and the logical approach. Instead, they tend to use lexical ambiguity when forming syntax constructions, confuse the coherent reason-consequence relationship, tend to extensively use language that is not very informative or start a sentence focused on one idea and complete it by empasizing a different one. Language mistakes and typographical errors are also noticeable.
Keywords: functional style, academic style, style features, style drawbacks